Image of fatherhood in printed media: document analysis - Maria Beatriz de Assis Veiga; Alyne Corrêa de Freitas; Simone Aguiar; Nayara Araújo de Souza; Fernando Porto; Adriana Lemos (Universidad de Alicante, 2017)
Aim: To identify the media records of the press communication representing paternity and to comment how they represent the father approaching his commemorative day. Method: Exploratory study, carried out through documental analysis, by means of "O GLOBO" newspaper, from August 01 to 11, 2013, some days before the Father´s day. Result: 106 media records were identified: 66,26% advertising records and 37,73% reports. The father figure appeared on every day of this time delimitation. Discussion: Paternity occurred amidst sociocultural and gender issues that permitted to perceive today a father figure more affective and involved on the child care. Conclusion: There is a business investment around the father figure, nevertheless, not only commercial factors, but also cultural and social ones influence on practicing paternity.